Pre-eksistensi Putra Allah: Studi atas Surat Paulus - Prayidno, Iswadi (Lux et Sal, 2022)
The deity of Jesus Christ, the Son of God, has been being the object of contemplation for the faithful since the beginning of Christianity. One of the reflected points is the pre-existence of the Son of God. The Church Fathers, especially around the Council of Nicaea, tussled a lot with this issue. They used philosophical terms which were quite complicated in their time. Strangely, long before that, Paul as a radical monotheist, who later became a follower of Christ, seemed to speak about the pre-existence of this Son effortlessly. This fact is interesting to be observed. Therefore, this article is intended to discuss Paul's views regarding the divinity of Jesus Christ.